Identification and Evaluation of Agile Criteria in the Iranian Telecom Industry Based on Digital Transformation Trends - Ghanbarian Alavijeh, Hamid; Hashemzadeh, Gholam Reza; Abbaspour Esfeden, Ghanbar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to identify and analyze the agility criteria within Iran’s telecom industry based on digital transformation trends. Methodology: The research employs a mixed-method approach, combining both qualitative and quantitative techniques. Initially, the Fuzzy Delphi Method was used to screen and rank the identified agility criteria through expert surveys. The Fuzzy DEMATEL Method was then applied to explore the causal relationships between the criteria, using pairwise comparisons to analyze the influence and susceptibility of each criterion. The study utilized a five-level fuzzy scale for data collection and analysis, with the final results being defuzzified for clearer interpretation. Findings: The study identified four key agility criteria: (1) Flexible and Dynamic Organizational Structure, (2) Skilled and Multi-Functional Workforce, (3) Data-Driven and Fast Decision-Making, and (4) Adoption of Advanced Technologies. The Flexible and Dynamic Organizational Structure was found to be the most influential criterion, while Data-Driven Decision-Making had the highest simultaneous influence and susceptibility. The research also highlighted the importance of skilled human resources and the adoption of advanced technologies as critical factors driving organizational agility. Conclusion: The findings emphasize the necessity for telecom companies to prioritize agility as a core element in their digital transformation strategies. By focusing on the identified key criteria, telecom companies can better navigate the challenges of a rapidly changing environment, improve their responsiveness to market demands, and enhance overall organizational performance. The study provides actionable insights for industry leaders to incorporate agility into their organizational culture and strategic planning, ensuring sustained competitiveness in the digital era.